Implementasi Kurikulum Merdeka Melalui Media Pembelajaran Berbasis Augmented Reality Matapelajaran Ilmu Pengetahuan Alam dan Sosial - Rifqi Hammad; Apriani; Abdul Muhid (Jurnal Pemberdayaan Masyarakat, 2025)
SLBN 2 Mataram is a special needs school with elementary, junior high and high school education levels. Currently the problem faced by SLBN 2 Mataram is the limited learning media for children with disabilities, the learning media used is still less attractive to students, the SLBN 2 Mataram teacher has never developed Augmented Reality-based learning media, the SLBN 2 Mataram school website has not seen the content and content.  Whereas making the content and content of the school website is very important for the existence of the organization's existence especially in the education environment. The solution offered from these problems is training in making Augmented Reality-based teaching media and training in making website content and content. There are several stages of activities carried out related to the solutions offered, starting from the stages of socialization, training, application of technology, mentoring and evaluation, and program sustainability. From the results of training activities obtained that there are 95.8% of teachers who can make Augmented Reality-based learning media and there are 90% of teachers who are able to manage and content the school website.